Sport related stress fracture of the clavicle with non-union: Case report and review - Constantinou, Demitri (Medknow Publications, 2008)
Stress fractures are relatively uncommon sports injuries and when they do occur, are mostly found in the lower limb. Stress fractures of the clavicle are particularly rare, having been described in a number of non-sport related pathologies, such as nervous tics and post radical neck dissection. In sport, there have only been seven cases reported in the literature. We report on a clavicle stress fracture in a 47-year-old male, partaking in recreational weight lifting activities. This is the first reported case of a non-union stress fracture of the clavicle. The patient underwent an open reduction and internal fixation and made a full recovery.